Comparison of intramuscular diclofenac and paracervical block during and after hysterosalpingography in women with infertility in South-South Nigeria: A randomized controlled trial - Enefia Kelvin Kiridi; Peter Chibuzor Oriji; Emily Gabriel Enefia Kiridi; Akaninyene Eseme Ubom; Johnpatrick Uchenna Ugwoegbu; Isaac Joel Abasi; Panebi Yao Bosrotsi (Nigerian Journal of Medicine, 2022)
Background: Tubal patency testing is essential in the evaluation of infertile women, and the preferred investigation for determining tubal patency is hysterosalpingography (HSG). Aim: The aim of the study was to compare the effectiveness of intramuscular diclofenac and paracervical block for pain alleviation during and after HSG. Patients, Materials and Methods: This research was carried out at the Infertility and Radiology Units of four health facilities, from January 2021 to April 2022. The Pan African Clinical Trials Registry received this trial's registration (PACTR202203726718710). Through simple randomization, 520 women billed for HSG were assigned into Groups I (control) and II (study). Group I had 75 mg of intramuscular diclofenac, while Group II had paracervical block with 2% lignocaine hydrochloride. At various stages of HSG, pain scores were obtained. Statistical Product and Service Solutions for Windows® version 25 (SPSS Inc.; Chicago, USA). The Chi-square test was used to examine the number of women in Groups I and II who experienced pain at the various stages of HSG, while the Student's t-test was used to compare sample means. Results: The step that caused the most pain was injection of contrast media, with a mean pain score of 3.85 ± 1.43 in Group I, and 5.00 ± 0.63 in Group II. Group I reported considerably lesser pain during speculum insertion, contrast media injection, and 24 h after the surgery (P = 0.001, P = 0.001, and P = 0.005, respectively). Conclusion: Intramuscular diclofenac is more effective than paracervical block (with lignocaine) for pain alleviation, both during and after HSG.